A chromosome-level Dendrobium moniliforme genome assembly reveals the regulatory mechanisms of flavonoid and carotenoid biosynthesis pathways - Jiapeng Yang; Qiqian Xue; Chao Li; Yingying Jin; Qingyun Xue; Wei Liu; Zhitao Niu; Xiaoyu Ding (Acta Pharmaceutica Sinica B)
Dendrobium moniliforme (D. moniliforme) is a traditional medicinal herb widely cultivated in Asia. Flavonoids, one of the largest groups of secondary metabolites in plants, are significant medicinal components in Dendrobium species. Several subgroups of R2R3-MYB proteins have been validated to directly regulate flavonoid biosynthesis. Using PacBio sequencing technology, we assembled a high-quality chromosome-level D. moniliforme genome with a total length of 1.20 Gb and a contig N50 of 3.97 Mb. The BUSCO assessment of genome annotation was 91.4%. By integrating the genome and transcriptome, we identified biosynthesis pathway enzyme genes related to flavonoids, polysaccharides, carotenoids, and alkaloids. A total of 90 R2R3-MYBs were identified in D. moniliforme and classified into 21 subgroups. Studies on the functions of R2R3-MYB transcription factors revealed that R2R3-MYB in SG6 can up-regulate flavonoid biosynthesis. Various validation experiments, including subcellular localization, transient overexpression, UPLC–MS/MS, HPLC, yeast one-hybrid, and dual-luciferase assays, demonstrated that DMYB69 directly up-regulates the expression of enzyme genes involved in flavonoid biosynthesis, increasing the content of flavonoids such as anthocyanin, flavone, and flavonol. Additionally, DMYB44 was shown to directly up-regulate the expression of carotenoid biosynthesis enzyme genes, thereby increasing carotenoid content. This study provides an essential genome resource and theoretical basis for molecular breeding research in D. moniliforme.